A novel combined-mode design for a MEMS-based micro passive direct methanol fuel cell / Umi Azmah Hasran ... [et al.] - Hasran, Umi Azmah; Kamarudin, Siti Kartom; Majlis, Burhanuddin Yeop; Sugandi, Gandi (Universiti Teknologi MARA, 2024)
A small-scale micro direct methanol fuel cell was developed by utilizing silicon substrate-based electrode plates, where the flow field plate was fabricated with micro-electro-mechanical system technology. Modelling work was carried out to assist in designing the anode and cathode plates to obtain the required configuration and geometric dimensions for the microfabrication process. A novel combined-mode anode plate was developed with an active-mode grid design and a passive-mode porous design for the flow field while the cathode plate was developed with a passive-mode design of square window-shaped through holes in a staggered arrangement. Silicon etching methods were used to form the desired flow field structures on the electrode plates with an active area of 1 cm2. The single cell was assembled by incorporating the electrode plates and membrane electrode assembly. A study on the feasibility and effectiveness of the new micro fuel cell was conducted. The performance test resulted in a maximum power density value of 1.86 mW/cm2 at a voltage of 138.7 mV.